“This is what I like and what I am going to study”: A qualitative study of academic decisions in high school - Rodríguez Menéndez, Mª del Carmen; Peña Calvo, Jose Vicente; Inda Caro, Mª de las Mercedes (Revista Complutense de Educación, 2016)
During high school students begin to explore occupations and professional expectations, form their self-efficacy beliefs and strengthen their academic interests. In this context, the paper presents the results of a research conducted in the Principality of Asturias to know high school students’ and their parents’ perceptions and opinions about academic choices made in secondary education, with particular emphasis on contextual factors that may help or hinder vocational development. We have used a qualitative methodology based on the use of the focus group. We have organized five focus groups with students and two focus groups with parents. The total number of people who participated in the focus group was 51 students and 14 fathers / mothers. The results obtained allow us to conclude that high school is still considered the gateway to university and not to vocational education and training studies (VET). It is also concluded that students base their academic decisions on personal taste and preference for certain options and this reason prevails over others such as professional opportunities or prior academic achievement. Regarding the influence of different social agents in the process of academic decision, the results are conclusive to say that their parents are the main support of the students. The article concludes with some suggestions for the improvement of educational guidance in institutions of secondary education.